Dampak Penerapan IFRS terhadap Nilai Perusahaan (Studi pada perusahaan Sektor Tekstil yang Listing di BEI) - Tutik Arniati (STIE Malangkucecwara, 2014)
The objective of this study is to examine corporate value differences among companies before and after convergence of International Financial Statement Reporting (IFRS). There are 18 componies in textile sector which used sampling, and this study uses secondary data from the Indonesian Capital Market Directory (ICMD). Measurement corporate value use Tobin?s Q ratio. Q is the market value of a company by comparing the market value of a company listed on the financial markets with a replacement value of the assets of the company. If Q is greater than 1 then the market value is greater than the value of assets of companies listed, it indicates that the stock is overvalued. Based on the paired t-test on a sample value of a company that has been presented, showing that the hypothesis is rejected because the probability value is not significant. That is means there are no significant difference in the corporate value before and of the company after IFRS convergence.